Peningkatan Kapasitas Koperasi Pondok Pesantren Se-Kabupaten Kudus, Melalui Sistem Akuntansi Berbasis Open Source untuk Meningkatkan Akuntabilitas Publik: Pengabdian - Arief Hidayat; Sri Retnoningsih; Puja Pratama; Sabrina Syafa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Islamic Boarding School Cooperatives (Kopontren) operating in Islamic Boarding Schools often face challenges in financial management. Furthermore, public accountability is crucial in this regard, given that the growth of the cooperative movement within Islamic boarding schools is a manifestation of the concepts of mutual assistance (ta'awun), brotherhood (ukhuwah), seeking knowledge (tholabul ilmi), and various other aspects. The purpose of this Community Service Activity is to improve financial management capabilities through the use of an Open Source Accounting System. Furthermore, transparency in financial reports produced by Kopontren is necessary to increase accountability. The method used in this community service activity is service learning. The results of this activity reflect its positive contribution in supporting the sustainable growth of Kopontren and increasing public accountability. This also empowers Kopontren owners to manage their cooperatives more effectively.